Vanadium Based Nanoelectrode Materials in Energy Storage Systems - Parasuraman, Aishwarya; Mariana, Lim T.; Skyllas-Kazacos, Maria (Nanoscience & Nanotechnology-Asia, 2013)
The performance and reliability of energy storage systems largely depend on the characteristics and properties of the electrode materials that constitute the system. Nanostructured materials have greatly influenced the overall performance of these systems by enhancing surface processes and improving the transport kinetics of the ions/molecules involved. Vanadium based materials have received considerable attention, particularly as electrode materials in high energy density Lithium ion batteries (LIB) and supercapacitors because of their cost effectiveness, efficient energy utilization and special structural characteristics. In this review, the applications of vanadium based materials as electrode components in energy storage systems have been described; their utilization in LIB and supercapacitors has been particularly highlighted. Recent developments in the field of vanadium based nanoelectrode materials are also discussed.
Keywords: Vanadium